Surviving against odds : the marginalized in a globalizing world - SinghaRoy, Debal K., 1957- (New Delhi : Manohar Publishers & Distributors, 2010)
Contributed articles with reference to India; most of the papers were presented in the international conference on social development, social movements and the marginalized, held at New Delhi in February 2008.
Includes bibliographical references.
Keywords: MARGINALITY--SOCIAL -- INDIA -- CONGRESSES; COMMUNITY DEVELOPMENT -- INDIA -- CONGRESSES; SUSTAINABLE DEVELOPMENT -- INDIA -- CONGRESSES; GLOBALIZATION -- ECONOMIC ASPECTS -- CONGRESSES; NEOLIBERALISM -- CONGRESSES